Stability of Insertion Sequence IS1245, a Marker for Differentiation of Mycobacterium avium Strains - Bauer, Jeanett (American Society for Microbiology, 1999)
Recently a novel insertion element, IS1245, has been described and suggested for use as a probe in restriction fragment length polymorphism studies of Mycobacterium avium strains. An important issue in this context is the stability of the insertion element. We analyzed single colonies of M. avium cultures and found frequent small one- to two-band changes. However, following repeated in vitro passages over 1 year, similar one- to two-band changes were observed in the IS1245 patterns of only six M. avium strains investigated.